An Operative Approach for Effective Segmentation of Retinal Blood Vessels Based on Multilevel DNN - Gupta, Sachin; Puthillath, Beena; Sharma, Meenakshi; Wagh, K. S.; Wagh, Sharmila K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Vision is obstructed by issues with the retina’s blood vessels. Given the rise in patients with visual problems, the frequency of periodic eye exams has increased. Decreasing numbers of ophthalmologists make the screening procedure challenging. Thus, for this field, automated computer-aided diagnostics are required. Over the past few decades, research has advanced to the point that it can now distinguish the different types of illnesses that affect vessels. Risky retinal vessels confirm the occurrence of CAD, DR hypertension, cerebral vascular issues, and stroke. A significant stage of DR called neovascularization involves the growth of many blood vessels without the bifurcation pattern and stiffness and minimal blood loss injuries. Arteriovenous junctions and vesicle width help to identify hypertensive retinopathy in patients. Retinal telangiectasia is a macular condition that affects the retina. The small blood vessels close to the fovea get enlarged or leak blood due to infection. The AV ratio and intersection also provide information on several vessel-related diseases. The suggested DNN is compared to traditional segmentation methods quantitatively and is found to have superior SN while still maintaining respectable SP and Acc. In addition, the area under the curve (AUC) is determined to verify accurate vascular segmentation from the retina. An improved post processing method will aid in accurate binary segmentation and preserve delicate blood vessel structures.